Geographies of Love - Lenz, Christian (transcript Verlag, 2016)
»Geographies of Love« is the first study to explore the cultural lifeworlds of British, Australian and Indian chick- and ladlit characters. Offering unique case studies including »Bridget Jones's Diary«, »About a Boy« and »Almost Single«, the book explores how women and men search for love and how they commit themselves to romances in specific spaces and places: the home and the office as well as shops, clubs and bars.This cross-disciplinary study provides scholars, students and keen readers with multiple points of access and easily-relatable situations. It applies the complex phenomenon of cultural geographies within the field of literary studies and sheds new light on a most passionate feeling
Keywords: Hochschulschrift; Culture; India; Cultural Geography; Cultural studies; Place; Literature; Literary Studies; British Studies; Chicklit; Ladlit; Romance; Great Britain; Australia; Anthropogeografie; Ort; Liebe; Trivialer Frauenroman; Englisch